Artificial Intelligence: an emerging tool for studying drug-induced liver injury. - Niu, Hao; Álvarez-Álvarez, Ismael; Chen, Minjun (Wiley, 2025)
Drug-induced liver injury (DILI) is a complex and potentially severe adverse reaction to drugs, herbal products or dietary supplements. DILI can mimic other liver diseases clinical presentation, and currently lacks specific diagnostic biomarkers, which hinders its diagnosis. In some cases, DILI may progress to acute liver failure. Given its public health risk, novel methodologies to enhance the understanding of DILI are crucial. Recently, the increasing availability of larger datasets has highlighted artificial intelligence (AI) as a powerful tool to construct complex models. In this review, we summarise the evidence about the use of AI in DILI research, explaining fundamental AI concepts and its subfields. We present findings from AI-based approaches in DILI investigations for risk stratification, prognostic evaluation and causality assessment and discuss the adoption of natural language processing (NLP) and large language models (LLM) in the clinical setting. Finally, we explore future perspectives and challenges in utilising AI for DILI research.
https://openpolicyfinder.jisc.ac.uk/id/publication/11895
Keywords: Inteligencia artificial en medicina; Proceso en lenguaje natural (Informática); Hígado - Efectos de los medicamentos; Hígado - Enfermedades; Aprendizaje automático (Inteligencia artificial); Hepatotoxicidad; Artificial intelligence; Drug-induced liver injury; Hepatotoxicity; Large language model; Machine learning; Nature language processing